MR Imaging of the Cavernous Sinus: Value of Spin Echo and Gradient Recalled Echo Images - Daniels, David L.; Czervionke, Leo F.; Bonneville, Jean F.; Cattin, F.; Mark, Leighton P.; Pech, Peter; Hendrix, Lloyd E.; Smith, David F.; Haughton, Victor M.; Williams, Alan L. (American Journal of Neuroradiology, 1988)
A detailed evaluation of the MR appearance of the pituitary gland–cavernous sinus junction has not been described. In a series of coronal T1-weighted spin echo images without and with IV gadolinium, we noted the variable size and signal intensity of cavernous venous spaces adjacent to the pituitary gland and the inconsistent visualization of the dural membrane just lateral to the gland. Correlation of coronal T1-weighted spin echo and gradient recalled echo images (the latter with high-signal-intensity vascular structures) proved to be an effective means of identifying cavernous venous spaces, connective tissue and cranial nerves, and the lateral margins of the pituitary gland, and of differentiating tumor tissue from cavernous venous spaces. Further work is needed to develop criteria to distinguish cavernous sinus compression from actual tumor invasion.